Green synthesis of hydrotalcite from untreated magnesium oxide and aluminum hydroxide - F. J. W. J. Labuschagné (Green Chemistry Letters and Reviews, 2018)
The influence of reaction temperature and time on the hydrothermal dissolution-precipitation synthesis of hydrotalcite was investigated. Untreated MgO, Al(OH)3 and NaHCO3 were used. An industrially beneficial, economically favourable, environmentally friendly, zero effluent synthesis procedure was devised based on green chemistry principles, in which the salt-rich effluent typically produced was eliminated by regenerating the sodium bicarbonate in a full recycle process. It was found that the formation of hydromagnesite dominates at low temperatures independent of reaction time. With an increase in reaction time and temperature, hydromagnesite decomposes to form magnesite. At low temperatures, the formation of hydrotalcite is limited by the solubility of the Al(OH)3. To achieve a hydrotalcite yield of 96%, a reaction temperature of 160°C for 5 h is required. A yield higher than 99% was achieved at 180°C and 5 h reaction time, producing an layered double hydroxide with high crystallinity and homogeneity.